PENGARUH MANAJEMEN LABA DAN RASIO KEUANGAN TERHADAP PERINGKAT OBLIGASI PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Labu, Yuliana Apriliani; Amtiran, Paulina Yuritha; Makatita, Reyner F. (Universitas Nusa Cendana, 2024)
This study examines the effect of earnings management and financial ratios on bond ratings. The variables used are 1) The effect of earnings management on bond ratings, 2) The effect of liquidity ratio on bond rating, 3) The effect of activity ratio on bond rating, 4) The effect of solvency ratio on bond rating, 5) The effect of profitability ratio on bond rating. The samples used in the study based on criteria are food and beverage companies that have consecutive bond ratings from 2015 to 2020. From the results of purposive sampling logistic regression, which includes descriptive statistical tests, research model tests, and logistic regression tests. The results of hypothesis testing show that earnings management, liquidity ratio, and profitability ratio have no significant effect on bond ratings, while activity ratio and solvency ratio have a significant effect on bond ratings. Keywords: Earnings Management; Financial Ratio; Activity Ratio; Bond Rating; Liquidity Ratio, Profitability Ratio; Solvency Ratio